Temporal Patterns and Intra- and Inter-Cellular Variability in Carbon and Nitrogen Assimilation by the Unicellular Cyanobacterium Cyanothece sp. ATCC 51142 - Polerecky, Lubos; Masuda, Takako; Eichner, Meri; Rabouille, Sophie; Vancová, Marie; Kienhuis, Michiel V. M.; Bernát, Gabor; Bonomi-Barufi, Jose; Campbell, Douglas Andrew; Claquin, Pascal; Červený, Jan; Giordano, Mario; et al. (Frontiers in Microbiology, 2021)
Unicellular nitrogen fixing cyanobacteria, UCYN, are abundant members of phytoplankton communities in a wide range of marine environments, including those with rapidly changing nitrogen (N) concentrations. We hypothesized that differences in N availability (N2 vs. combined N) would cause UCYN to shift strategies of intra-cellular N and C allocation. We used TEM and nanoSIMS imaging to track assimilation and intra-cellular allocation of 13C-labeled CO2 and 15N-labeled N2 or NO3 at different periods across a diel cycle in Cyanothece sp. ATCC51142. We present new ideas on interpreting these imaging data, including the influences of pre-incubation cellular C and N contents and turnover rates of inclusion bodies. Our results confirm the central role of the ornithine-ammonia cycle in N management (storage and mobilization) during diazotrophic growth. Within cultures growing diazotrophically, distinct sub-populations were detected that fixed N2 at night or in the morning. Additional significant within-population heterogeneity was likely caused by differences in the relative amounts of N assimilated into cyanophycin from sources external and internal to the cells. Whether growing on N2 or NO3, cells prioritized cyanophycin synthesis when N assimilation rates were highest. N assimilation in cells growing on NO3 switched from cyanophycin synthesis to protein synthesis, suggesting that once a cyanophycin quota is met, it is bypassed in favor of protein synthesis. Growth on NO3 also revealed that, at night, there is a very low level of CO2 assimilation into polysaccharides simultaneous with their catabolism for protein synthesis. This study revealed multiple, detailed mechanisms underlying C and N management in Cyanothece that facilitate its success in dynamic aquatic environments.